Characteristics of the Labour Market and Innovations in the Digital Economy: Exploring Their Relationship in OECD Countries - Woźniak-Jasińska, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: This paper examines the relationship between labour market characteristics and innovations in the OECD countries. Specifically, this study adopts a quantitative approach, primarily focused on employing correlation analysis to explore the relationship between labour market institutions, labour market outcomes, and indicators measuring innovations in the OECD countries. Research Design & Methods: The study uses data from a diverse range of OECD countries to analyse the relationship between institutional frameworks, labour market outcomes and various dimensions of innovation. Through a correlation analysis of key indicators such as innovation and technological adoption rates, employment and participation patterns, and labour market institutions, the study highlights various ways in which labour markets respond to the demands of an increasingly digitised economy. Findings: The results indicate that investments in information and communication technology in the OECD countries are positively associated with public spending on labour market policies. Additionally, the empirical analysis indicates a positive relationship between people employed in high-skill occupations and indicators measuring innovation. In contrast, the relationship between people employed in low and medium-skill occupations and indicators measuring innovation was negative. Furthermore, stricter employment protection legislation is usually associated with lower values in indicators measuring innovation in the OECD countries. The results also indicate that the relationship between indicators measuring innovation and employment can vary across different sectors. Implications / Recommendations: The findings underline the critical importance of institutional dynamics in fostering digital progress and provide essential insights for researchers, policymakers, and others interested in the labour markets in the digital age. Contribution: The originality of the study lies in its extensive discussion of the impact of innovation and new technologies on labour markets in the digital economy, as well as its analysis of relationships between labour market outcomes, labour market institutions and indicators measuring innovation.